Gastric cancer: Clinic presentation and general aspects - Ríos-Pérez, Jorge (2021)
Gastric cancer is one of the most common cancers globally, and the most lethal cancer in Peru. The variations in its incidence and mortality throughout the world are undergoing dramatic shifts in certain populations. This, along with the recent recognition of the broad molecular landscape of gastric tumors, will have an impact on the treatment decisions of our patients. The impact of these observations could be more significant in populations that are currently being affected by disparities in the care of gastric cancer.